The Association between Intended Mode of Delivery and Maternal Morbidity in Twin Pregnancies - Zafman, Kelly B.; Naqvi, Mariam; Melka, Stephanie; Miller, James; Rebarber, Andrei; Fox, Nathan S. (American Journal of Perinatology, 2019)
Objective To compare maternal morbidity between women undergoing delivery of twins who intend to labor with those women who do not intend to labor.Study Design This was a retrospective cohort study of women undergoing delivery of twins in a single maternal–fetal medicine practice between January 2005 and February 2018. We identified women with a twin delivery at gestational age ≥24 weeks and determined if they intended or did not intend to labor. Maternal outcomes were compared between the groups.Results A total of 788 patients were included, of whom 404 (51.3%) intended to labor and 384 (48.7%) did not intend to labor. Women who intended to labor had a high rate of vaginal delivery (VD; 79.7%). Overall, 45 (5.7%) women required blood transfusion; this was not significantly different between the groups (6.2 vs. 5.2%, p = 0.54). Women who intended to labor had a shorter hospital stay and lower blood loss. There were no significant differences for all other maternal outcomes.Conclusion In patients undergoing twin delivery, women who intend to labor have similar maternal morbidity compared with women who do not intend to labor. This supports current guidelines recommending providers offer a trial of VD for twin pregnancies.
Keywords: gestational; cesarean delivery; maternal morbidity; mode of delivery; complications